Analisis Kebutuhan Pengembangan Media Pembelajaran Flipbook Pada Pembelajaran IPA Untuk Siswa Kelas V Sekolah Dasar - Sri Mujiatun; Sumarno Sumarno; Ida Dwijayanti (Lembaga Pengembangan Kinerja Dosen, 2023)
Learning media is something that acts as an intermediary between the provider of information (teachers) to the recipients of information (students) with the aim of providing a stimulus to students so that they are motivated and can follow the learning process as a whole and meaningfully. Flipbook media is a combination of text, animation, sound, video, and so on. Flipbook in accordance with current curriculum developments. This is due to the emphasis on science lessons on modern pedagogic dimensions in learning. This study aims to describe the use of flipbooks in science learning using the PBL model with the SETS approach. This type of research includes qualitative descriptive research. The use of appropriate learning media, models and approaches can optimize students' understanding in learning. The research results of learning objectives can be achieved because it is supported by the use of learning media. In order for learning to run effectively and efficiently, the selection of learning media must be arranged appropriately and in accordance with the needs of students so that learning objectives can be achieved.